1998
DOI: 10.21273/horttech.8.4.573
|View full text |Cite
|
Sign up to set email alerts
|

Root Pruning and Soil Type Affect Pecan Root Regeneration

Abstract: Taproots of 2-year-old `Apache' seedling pecan [Carya illinoensis (Wang)] trees were pruned to 1 ft (30 cm), 2 ft (60 cm), or 3 ft (90 cm) in combination with wounding treatments consisting of no wounding, scraping through pericycle tissue on one or two sides of the taproot, or longitudinally splitting the taproot for about half its length. The trees were planted in a Port silt loam soil and a Teller sandy loam soil and grown without irrigation. At the end of the first and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Our data showed that root pruning shortly after germination had no effect on aboveground growth in the first year, but significantly increased the taproot branches. Additionally, similar to previously published findings (Harris et al, 2001;McCraw and Smith, 1998), the number of taproot branches increased with decreasing taproot length (Table 2). Further investigation would be required to evaluate whether these new root systems with more taproot branches would hold on or affect aboveground growth for longer periods of time.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our data showed that root pruning shortly after germination had no effect on aboveground growth in the first year, but significantly increased the taproot branches. Additionally, similar to previously published findings (Harris et al, 2001;McCraw and Smith, 1998), the number of taproot branches increased with decreasing taproot length (Table 2). Further investigation would be required to evaluate whether these new root systems with more taproot branches would hold on or affect aboveground growth for longer periods of time.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were reported by Wood (1996) for 3-year-old seedlings, although lateral roots proliferated at the base of the severed tap root. Other researchers have reported that taproot pruning stimulates top growth, root branching, and growth during the first 2 years after transplantation (McCraw and Smith, 1998). In a 2-year study, pecan trees with a taproot that was pruned to 20 or 25 cm in length regenerated roots better and with a greater survival rate than trees pruned to a 76-cmlong taproot (Smith and Johnson, 1981).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The soil was well drained, with a depth to the water table of more than 80 inches. Tree roots on all trees were trimmed to 18 inches using cutting shears to fit into the augured hole without twisting roots (McCraw and Smith, 1998;Smith and Johnson, 1981 were assigned to one of three pruning treatments in a completely randomized design: 0%, 50%, and 75% pruning of above-ground height. After pruning, mean tree height was 136, 68, and 34 inches for the 0%, 50%, and 75% treatments, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Little information exists on the morphology of seedlings of Carya spp., other than C. illinoinensis, and on effects of root pruning on seedling shoot and root morphology of hickories. Often, investigations on the effects of root pruning with coarsely rooted species focus on seedlings past their first year of growth (McCraw and Smith, 1998) without considering modification of seedling root morphology through root pruning shortly after seed germination. Furthermore, there has not been any investigation of the effects IBA may have on lateral root branching of any Carya species.…”
mentioning
confidence: 99%